DIFFERENCES IMAGE QUALITY OF SIGNAL TO NOISE RATIO (SNR) IN SENSITIVITY ENCODING (SENSE) APPLIED ON MAGNETIC RESONANCE CHOLANGIOPANCREATOGRAPHY (MRCP) EXAMINATION SEQUENCES TSE T2 CORONAL - Hengky Saefulloh; Siti Masrochah; Fatimah Fatimah (Jurnal Imejing Diagnostik (JImeD), 2018)
Background : Magnetic Resonance Cholangiopancreatography (MRCP) is a non invasive imaging examinations, which are used to evaluate the tractus billiaris, pancreatic ducts and gall bladder. In the last decade, one way to lower the scan time is with the method of parallel imaging. Parallel imaging has a basic function is the reduction of the time of the scan, as well as maintain the contrast of the image without the need for a system of higher performance gradients. Reduction of scan time in parallel imaging has some benefits. First, it is very useful for sequences that depends on the scanning time is short as a single breath hold. Second, the overall inspection time can be reduced, especially in patients with complaints of pain are great at certain positions such as pain when lying down, in patients of children or in cases of civil defence emergency. Breath hold itself has the purpose to avoid the image of the blur of movement organs. When breathing there is movement of the thoracic and abdominal organs in the cavum. However, the characteristics of each person has different breath hold. When the patient's breath hold insufficient at the time scanning takes place then the resulting image results become less than optimal and may cause artifacts in the picture. The scanning time on the MRCP examination sequences long enough to cause patients to press the emergency buzzer, this caused the patient to feel less comfortable at the time of the examination to take place, and the resulting examination in repeated from the beginning. Therefore researchers wanted to apply the technique of parallel imaging in examination of MRCP on T2 Coronal because of parallel imaging has benefits that are very useful for sequences that depends on the scanning time is short like a breath hold.Methods : This type of research is research experiments. This research was conducted on MRI 1.5 Tesla in Hospitals Tarakan from Jakarta and carried out in 8 volunteers. The results of the performed image ROI value to get SNR, ROI was performed on the area of the right hepatic duct, left hepatic duct, gall bladder, common bile duct and cystic duct so the obtained average value for signal compared to the ROI on background (standard deviation noise). Data analysis was done by using different test with a test of T-test to tell the difference between the use of SENSE against SNR.Results : The results of the calculation of the value of the average SNR of image sequence, MRCP Sequences TSE T2 Coronal without the SENSE on the anatomy of the right hepatic ductus 54.49; left hepatic ductus 55.54; gall bladder 91.07; the common bile duct 68.94 and cystic duct 60.46. While the value of SNR in image sequence, MRCP Sequences TSE T2 Coronal TSE that use the SENSE on the anatomy of the right hepatic duct 45.77; left duct heatic 46.88; gall bladder 77.87; the common bile duct 60.72 and cystic duct 50.58Scan time difference that is the average value of the scan time on Coronal T2 TSE piece sequences without SENSE for 1 minute 32 seconds while in the Coronal T2 TSE piece sequences using SENSE during 49 seconds or reduced by 46.7% compared with sequences TSE standards without SENSE on examination MRCP T2 Coronal.Conclusion : Based on the results of the study explains that there is a difference between the use of SENSE against SNR in the T2 Coronal TSE sequence in MRCP examination with the highest level of the overall significance of the p-value 0.05. On the use of SENSE decline SNR but scan time becomes shorter 46,7% compared with no use of SENSE